2021
DOI: 10.1017/s0031182021000913
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of giardiasis in captive animals in zoological gardens with strain typing of assemblages in China

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…Our genetic analyses revealed that eight out of 10 G. duodenalis infections were caused by the assemblage B of the parasite, and that all the genetic variants detected (sub-assemblages AI, AII, and BIV) were zoonotic (70). This predominance of assemblage B over assemblage A has been confirmed in other NHP populations from Belgium and the Netherlands (71), China (72)(73)(74), Croatia (65), Italy (66), the Republic of Congo (49), Slovakia (67), Sweden (75), and Thailand (52). However, it should be noted that this trend is far from general, and the opposite result (preponderance of assemblage A over assemblage B) has also been reported in captive NHP belonging to the genera Alouatta and Ateles in Brazil (76,77) and in different NHP collections from Spanish zoological gardens (13,68).…”
Section: Discussionsupporting
confidence: 74%
“…Our genetic analyses revealed that eight out of 10 G. duodenalis infections were caused by the assemblage B of the parasite, and that all the genetic variants detected (sub-assemblages AI, AII, and BIV) were zoonotic (70). This predominance of assemblage B over assemblage A has been confirmed in other NHP populations from Belgium and the Netherlands (71), China (72)(73)(74), Croatia (65), Italy (66), the Republic of Congo (49), Slovakia (67), Sweden (75), and Thailand (52). However, it should be noted that this trend is far from general, and the opposite result (preponderance of assemblage A over assemblage B) has also been reported in captive NHP belonging to the genera Alouatta and Ateles in Brazil (76,77) and in different NHP collections from Spanish zoological gardens (13,68).…”
Section: Discussionsupporting
confidence: 74%